2017
DOI: 10.1097/md.0000000000005878
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating malignant from benign gastric mucosal lesions with quantitative analysis in dual energy spectral computed tomography

Abstract: To investigate the value of quantitative analysis in dual energy spectral computed tomography (DESCT) for differentiating malignant gastric mucosal lesions from benign gastric mucosal lesions (including gastric inflammation [GI] and normal gastric mucosa [NGM]). This study was approved by the ethics committee, and all patients provided written informed consent. A total of 161 consecutive patients (63 with gastric cancer [GC], 48 with GI, and 50 with NGM) who underwent dual-phase contrast enhanced DESCT scans i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
13
1
1
Order By: Relevance
“…Second, we investigated the associations of radiomic features extracted from different MDCT image phases and proved that portal venous phase images might be more appropriate and stable for radiomic feature extraction in gastric cancer (Text S9, Figure S10, Table S3, Table S4), which was partially consistent with previous studies. [29][30][31] Our results also showed that most of the selected features from different MDCT image phases showed close correlations, and morphological features may be more stable for different MDCT image phases. Third, clearer than previous studies, we specified ICC calculation models, making consistency tests by ICC more reasonable.…”
Section: Discussionsupporting
confidence: 63%
“…Second, we investigated the associations of radiomic features extracted from different MDCT image phases and proved that portal venous phase images might be more appropriate and stable for radiomic feature extraction in gastric cancer (Text S9, Figure S10, Table S3, Table S4), which was partially consistent with previous studies. [29][30][31] Our results also showed that most of the selected features from different MDCT image phases showed close correlations, and morphological features may be more stable for different MDCT image phases. Third, clearer than previous studies, we specified ICC calculation models, making consistency tests by ICC more reasonable.…”
Section: Discussionsupporting
confidence: 63%
“…The growth and progression of solid tumors depend upon the formation of new blood vessels, which is different from normal tissues or benign lesions. Several studies have reported that CT imaging is useful for distinguishing small hepatocellular carcinoma from other hepatic lesions [ 23 , 24 ], small intrahepatic mass-forming cholangiocarcinoma from small liver abscess [ 25 ], malignant from benign pulmonary nodules [ 26 ], and gastric cancer from benign gastric mucosal lesions [ 11 ]. Indeed, the quantitative IC measurement is significantly higher in cancerous lesions compared to benign lesions, and its accuracy is greater than that of conventional CT.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the reason why PP is less effective than AP in distinguishing histological types may be due to the influence of blood flow. In addition, nICPP has been reported to exert a high sensitivity in differentiating malignant gastric mucosal lesions from normal gastric mucosa [ 11 ]. Furthermore, studies on the diagnostic efficacy of tumor differentiation degree are inconsistent [ 35 , 36 ], which may be due to the different biological behaviors of tumors and degrees of differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Contrast-enhanced CT is currently widely used for evaluating abdominal lesions because of its broad availability and convenience. [8][9][10] Jung Hoon 11 and Sun Kyung et al 12 have evaluated the imaging characteristics of atypical hypovascular PNET and PDAC, respectively. They found duct dilatation in CT may be a helpful predictor for PDAC.…”
Section: Introductionmentioning
confidence: 99%